A Parasite That Should not be Neglected in Patients with Ulcerative Colitis: Entamoeba histolytica - Murat Soylu; Abdurrahman Ekici; Selahattin Aydemir; Şehriban Yürektürk; Önder Akkaş (Türkiye Parazitoloji Dergisi)
Objective: To determine the prevalence of amoebiasis, which has been neglected in recent years according to the World Health Organization, in ulcerative colitis patients and investigate the relationship between amoebiasis and ulcerative colitis. Methods: The study included 150 individuals, including 100 ulcerative colitis patients and 50 healthy individuals without gastrointestinal complaints. The samples collected were first analyzed macroscopically and then using native-Lugol, trichrome staining, and enzyme-linked immunosorbent assay (ELISA). Results: In the microscopic examination, Entamoeba spp. cysts were found in 22% of the ulcerative colitis patients and 2% of those in the control group. Entamoeba histolytica (E. histolytica) adhesin antigen was detected by ELISA in 31% of the ulcerative colitis patients and 4% of those in the control group. A significant correlation was found between the incidence of E. histolytica and ulcerative colitis in the statistical evaluation. Conclusion: E. histolytica should not be neglected in ulcerative colitis patients and should be investigated in the presence of diarrhea, bloody diarrhea, and abdominal pain.